Size effects on double cantilever beam fracture mechanics specimen based on strain gradient theory. (January 2017) - Joseph, R.P.; Wang, B.L.; Samali, B.
Highlights: At small scale, for longer beams, the large deformation consideration is essential. The gradient model predicts stiffer bending behavior than the non-gradient models. The strain gradient effect is more prominent when h / l  ⩽ 0.2. The root effect of the DCB has significant influence when h / l  ⩽ 0.2 and a/h  < 20. Abstract: This paper investigates large deformation of a cantilever beam which is further employed to study the fracture behavior of double cantilever beam (DCB), based on strain gradient elasticity theory. Root effect of the DCB is also included for modelling and analyses. The numerical solutions of maximum tip deflection and strain energy release rate are presented. Results demonstrate that the consideration of large deformation is crucial at small scale, especially for more slender beams, as the bending behavior of the beam in that case is different from the classical results. The strain gradient and root effects of the DCB are more prominent when thickness of the beam is less than the material length scale parameter. The strain gradient model demonstrates significant stiffening behavior at the smaller scale. In general, the root effect may not be neglected if the length to thickness ratio of the beam is smaller. Overall, the strain energy release rate of the gradient model, even with the incorporation of root part, remains less than that of non-gradient model. This conclusion is entirely different from the classical method that neglects the uncracked part of the DCB.